The effectiveness of mindfulness-based relapse prevention on the prevention of relapse, craving and self-control in opiate-dependent individuals - alireza maredpour; Mahmmod Najafy; Farangiss amiri (Drug Control Headquarters, Research and Education Office, 2015)
Abstract Objective: the aim of this study is to investigate the effectiveness of mindfulness-based relapse prevention on the prevention of relapse, craving and self-control in opiate-dependent individuals in Yasuj. Methodology: This quasi-experimental study applied pretest - posttest and a control group. The sample included 30 male patients with drug addiction in Yasuj who were chosen from addiction clinics based on criterion sampling. To collect the required data the short form of Self-Control Scale developed by Tangney was applied. The mindfulness technique was performed on the experimental group for 8 sessions (2 hours each session, one session per week). Findings: Data were analyzed applying univariate analysis of covariance and Chi-square. Results showed that the mean scores of the experimental group decreased in comparison to the control group in terms of craving and increased with regard to self-controlling. In addition, the recurrence rate was lower for the experimental as compared to the pre-test. Conclusion: Mindfulness-based relapse prevention has practical functionality for clinical interventions to reduce craving and relapse rate among drug users and to increase self-control in addicts.